MONITORING KUALITAS AIR DAN IDENTIFIKASI JENIS PARASIT PADA PEMBENIHAN IKAN MAS (Cyprinus carpio) - Budiyati Budiyati; Ani Leilani; Eriyanti Wahid; Diana Putri Renitasari; Muhammad Hery Riyadi Alauddin; Alauddin Alauddin; Ni Putu Dian Kusuma (Universitas Mataram, 2024)
Diseases arise due to unbalanced interactions, namely pathogens, hosts and the environment. This collapse will affect the increase or decrease in disease in fish. This research aims to identify parasites and analyze water quality in Carp Fish hatcheries. Carp seed samples were taken randomly in research containers. The water quality parameters observed consisted of temperature, pH, DO, nitrate, nitrite, and ammonia. This research was conducted for one month at the Tatelu Freshwater Aquaculture Center (BPBAT). The results of the research show that there are three types of parasites found in the gills, mucus, and fins of Carp Fish, namely Tricodina sp, Dactylogyrus sp, and Gyrodactylus sp.